2021
DOI: 10.1002/chem.202101087
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing Dehydroisomerization Boosts n‐Butane Dehydrogenation with High Butadiene Selectivity

Abstract: Butadiene (BD) is a critical raw material in chemical industry, which is conventionally produced from naphtha cracking. The fast‐growing demand of BD and the limited oil reserve motivate chemists to develop alternative methods for BD production. Shale gas, which mainly consists of light alkanes, has been considered as cheap raw materials to replace oil for BD production via n‐butane direct dehydrogenation (n‐BDH). However, the quest for highly‐efficient catalysts for n‐BDH is driven by the current drawback of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Application of Ti-silicalite and LaAlO 3 -perovskite as supports as well as promotion by MgO and CaO increased the dispersion and sintering resistance of Pt nanoparticles and suppressed side reactions and coking. [102][103][104] Promotion with potassium was found to improve the efficiency of Cr-Al catalysts in isobutane DDH. In the activated catalysts, potassium preferably interacts with alumina and modifies the average dispersion of Cr 3+ O x species.…”
Section: Chem Soc Rev Review Articlementioning
confidence: 99%
“…Application of Ti-silicalite and LaAlO 3 -perovskite as supports as well as promotion by MgO and CaO increased the dispersion and sintering resistance of Pt nanoparticles and suppressed side reactions and coking. [102][103][104] Promotion with potassium was found to improve the efficiency of Cr-Al catalysts in isobutane DDH. In the activated catalysts, potassium preferably interacts with alumina and modifies the average dispersion of Cr 3+ O x species.…”
Section: Chem Soc Rev Review Articlementioning
confidence: 99%
“…Despite achievements in technologies for direct dehydrogenation of n -butene or n -butane/ n -butene mixtures (e.g., Houdry–Catadiene process), n -butene is generally used as the feedstock to achieve a high yield of 1,3-BD. Compared with significant improvements in product selectivity achieved for ethane and propane dehydrogenation, catalysts for direct n -butane dehydrogenation to 1,3-BD with high selectivity have proven more difficult to identify, , and in studies reported to date, the 1,3-BD selectivity is generally less than 20%. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Compared with significant improvements in product selectivity achieved for ethane and propane dehydrogenation, catalysts for direct nbutane dehydrogenation to 1,3-BD with high selectivity have proven more difficult to identify, 1,11 and in studies reported to date, the 1,3-BD selectivity is generally less than 20%. 8,12,13 Supported Pt catalysts and Pt bimetallic catalysts, particularly PtSn, have been widely explored for direct dehydrogenation of alkanes to alkenes. Catalysts containing very small Pt, PtSn, or PtZn nanoclusters have been shown to be highly active, selective, and resistant to coking.…”
Section: Introductionmentioning
confidence: 99%
“…6 The main advantages of direct dehydrogenation are environmental friendliness, economic efficiency, and competitive selectivity for the target products. 7 Despite these advantages, the relatively low conversion and C−C cleavage of direct butane dehydrogenation restrict production scaleup. 8,9 Furthermore, alkane dehydrogenation is a catalyst-structuresensitive reaction, and controlling the particle size of the catalyst can effectively tune the conversion and C−C bond cleavage behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with these existing technologies, direct dehydrogenation is a promising method for alkene production . The main advantages of direct dehydrogenation are environmental friendliness, economic efficiency, and competitive selectivity for the target products . Despite these advantages, the relatively low conversion and C–C cleavage of direct butane dehydrogenation restrict production scale-up. , …”
Section: Introductionmentioning
confidence: 99%